Effect of TV Commercials on Youth Consumer Behavior - Asrar, Zaeema; Hussain, Mudassir; Ahmed, Shams (Advances in Social Sciences Research Journal, 2017)
The aim of this study is to determine either there is effect of TV commercials on consumer behavior or and the youth consumer behavior influences positively by TV commercials. The elements of TV commercials such as jingles (songs), story, and celebrity endorsement enhance the youth to purchase the product or not. Consumers   follow the purchasing funnel that will be started with the awareness and giving awareness to the consumer about the product TV is the best medium to convey your message or to give awareness about a product. This study is conducted in Benazir Bhutto Shaheed University through the survey, 100 questionnaires were distributed among the youth (students). The analysis of the research is done through SPSS. The result shows that television commercials play the vital role in changing the youth consumer behavior because it is the best medium to give awareness about the product, services and ideas. It is the most significant way to reach the consumer for the purpose of giving awareness and it also the factor to enhance the youth toward a brand due to having audio and visual communication.